Role of urine analysis and radiology in the diagnosis of vesical calculi among patients of Darbhanga district, India - Arun, Ramesh Chandra; Prasad, Jagdish (International Surgery Journal, 2018)
Background: Bladder stone is a common disease in this part of our country. This study was undertaken to find out the role of urine analysis and radiology in the diagnosis of vesical calculi and average size of penis in such patients in Darbhanga district. Methods: This study was conducted among patients admitted with features of vesical Calculi in the upgraded Department of Surgery, Dharbhanga Medical College and Hospital, Dharbhanga. SPSS software was used for data analysis. Results: On routine urine examination oxaluria was observed in 63.3% of cases. On preoperative culture of urine, E. coli was the most common bacteria isolated (36.6%). Maximum number of stones were single, and most of them were found only in bladder by plain X-ray (K.U.B.). The average length of penis came down from 17 to 0.4 inch after one month of removal of stone. Conclusions: In the study plain X-ray (K.U.B.) was to be of great value in diagnosing the presence of stone.